Combination of Narrow-band Imaging and Autofluorescence Imaging Videobronchoscopy in the Assessment of Lung Cancer - Zhongbo CHEN; Yiming YU; Shifang SUN; Hongying MA; Qiaoli ZHANG; Dan LV; Bijiong WANG; Chao CAO; Qunli DING; Zaichun DENG (Chinese Journal of Lung Cancer, 2013)
Background and objective Narrow-band imaging (NBI) and autofluorescence imaging (AFI) are new bronchoscopy technologies that are important in lung cancer diagnosis. The aim of this study is to determine whether or not the combination of these two technologies can improve sensitivity and specificity of lung cancer diagnosis. Methods A total of 137 patients who manifested symptoms of lung cancer were investigated in this project. All of the examinations were performed based on an Olympus Evis Lucera bronchoscopy system. The patients were examined by white light bronchoscopy (WLB), NBI and AFI. At least three biopsies from body parts visualized as lesions were obtained from each patient. Results WLB sensitivity and specificity were 56.6% and 62.5%, respectively. NBI sensitivity and specificity were 71.3% and 75.0%, respectively. AFI sensitivity and specificity were 82.2% and 25.0%, respectively. The sensitivity and the specificity of the combined NBI and AFI were 94.6% and 87.5%, respectively. The sensitivity and the specificity of the combined NBI and AFI were significantly higher than those of AFI alone (P<0.01). Likewise, the sensitivity and the specificity of the combined NBI and AFI were significantly higher than those of NBI alone (P<0.05). Conclusion NBI or AFI exhibited higher sensitivity of lung cancer diagnosis than WLB. Combined NBI and AFI also showed significantly higher sensitivity and specificity than NBI or AFI.